2016
DOI: 10.1002/ceat.201500635
|View full text |Cite
|
Sign up to set email alerts
|

Intensified Distillation‐Based Separation Processes: Recent Developments and Perspectives

Abstract: Greater sustainability can be achieved by decreasing the production costs, energy consumption, equipment size, and environmental impact as well as improvement of the raw material yields, remote control, and process flexibility. Process intensification (PI) as the main route for improving the process performance is used widely in heat transfer, reactions, separation, and mixing, which results in plant compactness, cleanliness, and energy efficiency. Some of the main intensified separation processes and improvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 96 publications
0
13
0
Order By: Relevance
“…The side‐reactor column (SRC) configuration is an innovative hybrid RD configuration, where a non‐reactive column is coupled with several side‐reactors through external streams 11. This construction allows reaction and separation occurring in different zones, breaking the constraint of consistent conditions of reaction and distillation and satisfying the requirement of amount of catalysts arrangement 12, 13.…”
Section: Introductionmentioning
confidence: 99%
“…The side‐reactor column (SRC) configuration is an innovative hybrid RD configuration, where a non‐reactive column is coupled with several side‐reactors through external streams 11. This construction allows reaction and separation occurring in different zones, breaking the constraint of consistent conditions of reaction and distillation and satisfying the requirement of amount of catalysts arrangement 12, 13.…”
Section: Introductionmentioning
confidence: 99%
“…Also, many studies suggested that, with proper optimization and robust control, more economic incentives can be derived out from the thermally coupled column 14, 17. However, although the energy potential of the internal thermally coupled column is well established, its high‐level complex dynamic behavior has remained a key challenge 18–23. Other notable characteristics that aggravate the challenge include inverse response and strong interactions between the bottom and overhead control loops 24.…”
Section: Introductionmentioning
confidence: 99%
“…Distillation, which is the workhorse of chemical process industries, is an energy-intensive process, so massive amounts of CO 2 are released during the process [13][14][15][16]. Therefore, the reduction of the CO 2 emissions in distillation systems has become a matter of urgent concern, and efforts were focused on energy-saving techniques and modifications [17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%